Plausibility Effects When Reading One- and Two-character Words in Chinese: Evidence from Eye Movements - Yang, Jinmian (2012)
Eye movements of Chinese readers were monitored as they read sentences containing a critical character that was either a one-character word or the initial character of a two-character word. By manipulating the verb prior to the target word, the one-character target word (or the first character of the two-character target word) was either plausible or implausible, as an independent word, at the point at which it appeared, whereas the two-character word was always plausible. The eye movement data showed that the plausibility manipulation did not exert an influence on the reading of the-two character word or its component characters. However, plausibility significantly influenced reading of the one-character target word. These results suggest that processes of semantic integration in reading Chinese are performed at a word level, instead of a character level, and that word segmentation must take place very early in the course of processing.